If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5 + -8w)(5 + 8w) = 0 Multiply (5 + -8w) * (5 + 8w) (5(5 + 8w) + -8w * (5 + 8w)) = 0 ((5 * 5 + 8w * 5) + -8w * (5 + 8w)) = 0 ((25 + 40w) + -8w * (5 + 8w)) = 0 (25 + 40w + (5 * -8w + 8w * -8w)) = 0 (25 + 40w + (-40w + -64w2)) = 0 Combine like terms: 40w + -40w = 0 (25 + 0 + -64w2) = 0 (25 + -64w2) = 0 Solving 25 + -64w2 = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + -64w2 = 0 + -25 Combine like terms: 25 + -25 = 0 0 + -64w2 = 0 + -25 -64w2 = 0 + -25 Combine like terms: 0 + -25 = -25 -64w2 = -25 Divide each side by '-64'. w2 = 0.390625 Simplifying w2 = 0.390625 Take the square root of each side: w = {-0.625, 0.625}
| 12-9y=-5 | | -7x+6-9=29 | | -4+3=-12+17x | | 3z/10-5=8 | | 5(2b-3)=3(b+9) | | 12(12n)+n-3=396 | | 1/8-X/7=3/56 | | F^2-22f=72 | | -4(1-7z)=-29 | | 5x-2/3=-49/10 | | 15x^4-15x^3=0 | | Z/7-2=6 | | f(x)=x^4+32 | | 8(p-a)-6=2(ap-5) | | 6x+7y(2-3y)=-21 | | 24x+9=21 | | 5x-7=4x-7 | | x/9-9=9 | | 9-(5a+1)+3a+7= | | -8h-6h=24 | | 4^3(8^(1/3)z^2 | | 6x+7y=-21 | | 3x+6(2)=x+11(4) | | 6x(2-3y)+7y=-21 | | 3ax-4x=0 | | 23=-3(5y+2) | | 66y/3-34y | | 8x^2-128x=0 | | 1+6y-15y= | | 1/3-K/8=7/24 | | -1(-1y+3)=1 | | -.4x^2+.2x=-2 |